ANALISIS PERBANDINGAN TINGKAT KONSERVATISME AKUNTANSI PADA BANK UMUM SYARIAH DAN BANK UMUM KONVENSIONAL DI INDONESIA - Resti Purnamasari; Inten Meutia; Emylia Yuniartie (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2018)
This study aims to analyze whether there are differences in the level of conservatism of Islamic Commercial Banks and Conventional Commercial Banks. Conservatism is an important principle in financial reporting that is intended so that the recognition and measurement of assets and profits is carried out with caution because economic and business activities are surrounded by uncertainty. The research sample is the Islamic Commercial Bank and Conventional Commercial Banks. From the results of the analysis, it can be concluded that there are significant differences in the level of accounting conservatism in Islamic Commercial Banks and Conventional Commercial Banks in Indonesia. Differences in the level of conservatism in Sharia Commercial Banks and Conventional Commercial Banks are influenced by the benefits of applying the principles of conservatism, rules, and accountability in both banks.